A transnational public inquiry into COVID-19 origins and global biosecurity: rebuilding trust with Confucian ethics and practical idealism - Nie, Jing-Bao (Frontiers in Communication, 2026)
Grounded in the notion of xin (trust) and practical idealism in Confucius’ Spring and Autumn (Chunqiu), this article proposes a transnational public inquiry into COVID-19 origins and global biosecurity amid the deepening international mistrust and escalating geopolitical conflict. Confucian ethics possesses critical and constructive moral power not only for envisioning a moral world order but also for offering practical socio-political mechanisms to realise it. The COVID-19 pandemic underscored the urgent need for far more robust transnational biogovernance to address growing human-made and natural biothreats, a task that depends on trust across nations and cultures. Yet an information war over the origins of COVID-19 erupted globally at the height of the pandemic and continues today. Through the Confucian ethical lenses, the dispute reflects a comprehensive crisis of transnational trust, driven by the increasing dominance of power politics and the advance of de facto Cold War II between China and the US, each with its allies worldwide. To move forward constructively, Confucian ethics mandates, morally and socio-politically, an unprecedented Janus-like international public inquiry into tracing COVID-19 origins and enhancing global biosecurity and health security, which constitute a major human rights concern of our times. Classical Confucianism, along with other moral traditions worldwide that share the spirit of practical idealism, can reshape global power politics by upholding basic human values and improving intercultural and international trust.